Religieuses du Sacré-Coeur de Jésus (RSCJ) as a Religious Social Movement - R.F. Bhanu Viktorahadi; Martha Gabriela Hernández (Parahyangan Catholic University, 2026)
This study aims to analyze whether Religieuses du Sacré-Coeur de Jésus (RSCJ) can be categorized as a religious social movement and to explain the characteristics of this movement based on the principal missions it has developed. The study employs a qualitative approach using the library research method and utilizes social movement theories developed by Sydney Tarrow, Max Weber, Talcott Parsons, and Neil J. Smelser as its analytical framework. The findings reveal that the emergence of RSCJ cannot be separated from the context of the French Revolution and the development of modernism, both of which encouraged various forms of social and religious reform. The study also demonstrates that RSCJ can be understood as a value-oriented religious social movement that translates the spirituality of the Sacred Heart of Jesus into collective action through education, interreligious dialogue, and the promotion of spirituality and a culture of peace. The implications of this study indicate that spirituality-based religious social movements play a strategic role in strengthening education, fostering interfaith dialogue, and developing a culture of peace within increasingly pluralistic and complex societies. The originality of this study lies in its effort to position RSCJ within the perspective of religious social movements, thereby expanding the fields of sociology of religion and social movement studies, which have traditionally focused on mainstream religious organizations and civil society–based social movements.